2015
DOI: 10.1097/rlu.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body 99mTc-Octreotide Scintigraphy With SPECT/CT to Detect Occult Tumor Inducing Paraneoplastic Osteomalacia

Abstract: A 32-year-old woman presented with progressive myalgia, bone pain, fatigue, insufficiency hip fractures, high urine phosphate, and low serum phosphate and vitamin D levels. These findings were suggestive of oncogenic osteomalacia. A whole-body Tc-octreotide scintigraphy with SPECT/CT showed uptake on a sclerotic intramedullary lesion in the left medial tibia plateau. MRI depicted a solid lesion. The lesion was surgically removed; the patient became asymptomatic, and follow-up laboratory results normalized. His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Positive staining was detected in a current study for somatostatin receptor in 14 PMT patients secreting FGF-23 (Houang et al, 2013). It was demonstrated that in PMTs expressing somatostatin receptors (SSTRS), wholebody Tc-octreotide scintigraphy with SPECT/CT can demonstrate occult oncogenic osteomalacia (Rodrigues et al, 2014). In 6 patients whose diagnosis was delayed in spite of serious symptoms, gallium-68 DOTATATE PET/ CT detected localized phosphaturic mesenchymal tumors…”
Section: To the Editorsupporting
confidence: 49%
“…Positive staining was detected in a current study for somatostatin receptor in 14 PMT patients secreting FGF-23 (Houang et al, 2013). It was demonstrated that in PMTs expressing somatostatin receptors (SSTRS), wholebody Tc-octreotide scintigraphy with SPECT/CT can demonstrate occult oncogenic osteomalacia (Rodrigues et al, 2014). In 6 patients whose diagnosis was delayed in spite of serious symptoms, gallium-68 DOTATATE PET/ CT detected localized phosphaturic mesenchymal tumors…”
Section: To the Editorsupporting
confidence: 49%
“…A stepwise approach is advocated, first performing functional tests. Tumours associated with osteomalacia variably express five somatostatin receptors (SSTR1-5), allowing SSTR-based functional imaging by somatostatin analogue scintigraphy or positron emission tomography [ 33 , 46 , 52 , 53 ]. Octreotide is somatostatin analogue used in treatment of some neuroendocrine tumours and acromegaly.…”
Section: Reviewmentioning
confidence: 99%
“…[6][7][8][9] Recently, 99m Tc labeled octreotide whole body scan also showed utilization in the evaluation of TIO. 10,[17][18][19] There is no direct comparison involving a large patient population between PET/CT-based tracers ( 68 Ga DOTANOC or 68 Ga DOTATATE) and FIGURE 5. A 59-year-old man had difficulty working with worsening diffuse bone pain, especially the right knee, for more than 3 years, for which he received sodium hyaluronate injection to the right knee, but therapy was not effective.…”
Section: Discussionmentioning
confidence: 99%